Murder most foul Hamlet through the ages - Bevington, David M. (Oxford : Oxford University Press, 2011)
David Bevington demonstrates that the staging, criticism, and editing of Hamlet go hand in hand over the centuries to such a remarkable extent that the history of Hamlet can be seen as a kind of paradigm for the cultural history of the English-speaking world.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616 -- Stage history